Effects of the Oxygen-Carrying Solution OxyVita C on the Cerebral Microcirculation and Systemic Blood Pressures in Healthy Rats - Abutarboush, Rania (MDPI, 2014)
The use of hemoglobin-based oxygen carriers (HBOC) as oxygen delivering therapies during hypoxic states has been hindered by vasoconstrictive side effects caused by depletion of nitric oxide (NO). OxyVita C is a promising oxygen-carrying solution that consists of a zero-linked hemoglobin polymer with a high molecular weight (~17 MDa). The large molecular weight is believed to prevent extravasation and limit NO scavenging and vasoconstriction. The aim of this study was to assess vasoactive effects of OxyVita C on systemic blood pressures and cerebral pial arteriole diameters. Anesthetized healthy rats received four intravenous (IV) infusions of an increasing dose of OxyVita C (2, 25, 50, 100 mg/kg) and hemodynamic parameters and pial arteriolar diameters were measured pre- and post-infusion. Normal saline was used as a volume-matched control. Systemic blood pressures increased (P ≤ 0.05) with increasing doses of OxyVita C, but not with saline. There was no vasoconstriction in small (<50 µm) and medium-sized (50–100 µm) pial arterioles in the OxyVita C group. In contrast, small and medium-sized pial arterioles vasoconstricted in the control group. Compared to saline, OxyVita C showed no cerebral vasoconstriction after any of the four doses evaluated in this rat model despite increases in blood pressure.